Conflicts to consensus: stakeholder perspectives of Tioman Island tourism sustainability - Chia, Kei Wei; Ramachandran, Sridar; Ho, Jo Ann; Ng, Serene Siew Imm (Universiti Malaysia Sarawak, 2018)
This paper presents the results of an exploratory study regarding island tourism at a rural Island destination in Malaysia. The findings based on qualitative semi-structured interviews with a number of stakeholder groups are reported, which show the different views among them where there is a divergence between the four stakeholder groups with regards to the problems faced by Tioman Island. A total of 46 residents, tourists, and government officials were interviewed to understand the problems encountered on Tioman Island. The qualitative interviews uncovered 15 problems faced by the various stakeholder groups on the island. The results found that different stakeholders perceived things differently. This study may help tourism planners, developers, and policy-makers to understand the problems faced by the island so that strategies can be implemented accordingly, to assess, monitor, and evaluate problems.